(untitled) (Eurasian Research Bulletin, 2023)
Currently, the study of medicinal plants, their effect on diseases, preparation of medicines from them are relevant topics. This article provides the latest information about the botanical classification, importance, medicinal properties and use of mint, one of the medicinal plants, in folk medicine